Implementation of the Project to Strengthen the Profile of Pancasila Students in the Independent Curriculum Class XI at Wira Bhakti Gorontalo Integrated High School - Maryam Lasena; Melizubaida Mahmud; Risca Marsanti Halid; Radia Hafid; Agil Bahsoan (International Journal of Social Science and Humanity, 2024)
This study aims to find out how the Implementation of the Pancasila Student Profile Strengthening Project in the Independent Curriculum Class XI at Wira Bhakti Gorontalo Integrated High School and find out what factors affect the implementation of the Pancasila Student Profile Strengthening Project in the Independent Curriculum Class XI. By using a qualitative research method, a Descriptive approach with a Narative Inquiry research design. Data collection techniques through interviews, observations and documentation. Data analysis is carried out by means of data reduction, data presentation, and conclusion drawn. The results of the study show that Wira Bhakti Gorontalo Integrated High School has carried out the Pancasila Student Profile Strengthening Project with the theme: Build the Soul and Body, Bhineka Tunggal Ika, Sustainable Lifestyle, Voice of Democracy, and Entrepreneurship. The implementation of the Pancasila Student Profile Strengthening Project has been running effectively and has undergone development. Its implementation has instilled the character of Pancasila. The factors that affect its implementation are supporting factors consisting of student motivation, support of parents/guardians of students, school environment, the existence of facilities and infrastructure, and cooperation with external parties/agencies. The inhibiting factors consist of teacher training related to P5, and the limitation of time and project schedules.